2012
DOI: 10.1063/1.4757669
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of turbulent structures in riblet channels up to Re τ≈ 550

Abstract: Articles you may be interested inEffect of the computational domain on direct simulations of turbulent channels up to Re τ = 4200

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 33 publications
18
42
0
Order By: Relevance
“…They established that the riblet-induced spanwise rollers, which are responsible for the drag-reducing break-down, scale in viscous units [12]. This result is consistent with the assumption that the riblet effect is limited to the viscous and buffer layers [13].…”
supporting
confidence: 78%
See 3 more Smart Citations
“…They established that the riblet-induced spanwise rollers, which are responsible for the drag-reducing break-down, scale in viscous units [12]. This result is consistent with the assumption that the riblet effect is limited to the viscous and buffer layers [13].…”
supporting
confidence: 78%
“…6) are both approximately conserved A longer computational domain would be necessary to determine accurately whether or not the drag reduction remains constant when the comparison is done with respect to one of those two Reynolds numbers. García-Mayoral and Jiménez [12] have already predicted a weak dependence of c f with Re τ , invoking that the riblet influence is restricted to the buffer layer.…”
Section: Reduction Of the Wall Frictionmentioning
confidence: 96%
See 2 more Smart Citations
“…That does not happen above the buffer layer, and is inhibited near the wall by the impermeability boundary condition but, if that condition is relaxed by porosity 63 or by other means, 50 the Kelvin-Helmholtz instability reappears, with vertical eigenfunctions that remain localized below x + 2 ≈ 30. 50,64 We have also analyzed the bursts in simulations of fully turbulent flows in computational boxes that are minimal with respect to the structures of the logarithmic layer. We have shown that they share many features with the linearized bursts, especially for the wall-normal velocity u 2 .…”
Section: Discussionmentioning
confidence: 99%